Large-Scale Pattern-Based Information Extraction from the World Wide Web - Blohm, Sebastian (KIT Scientific Publishing, 2021)
Extracting information from text is the task of obtaining structured, machine-processable facts from information that is mentioned in an unstructured manner. It thus allows systems to automatically aggregate information for further analysis, efficient retrieval, automatic validation, or appropriate visualization. This work explores the potential of using textual patterns for Information Extraction from the World Wide Web.